Effect of nitrate and irradiance on fatty acid production in microalgae cultivated for feeding larvae and broodstock conditioning in batch culture (Revista de Biología Marina y Oceanografía, 2019)
The aim of this study was to compare conditions for the production of high levels of PUFA, EPA and DHA in cultured microalgae for larval bivalve feeding stages. It assessed fatty acid composition by gas chromatography for Isochrysis galbana Parke (T-Iso) and 2 species of Chaetoceros, C. gracilis Pantocsek and C. constrictus Gran. Species were studied in batch cultures, at the beginning of stationary growth phase with different irradiance and 2 levels of nitrogen content for Chaetoceros sp., and constant irradiance with 5 concentrations of sodium nitrate for I. galbana in an F/2 medium. Isochrysis galbana produced higher levels of linolenic acid and docosahexaenoic acid than eicosapentaenoic acid (EPA) at low N-nitrate concentrations; however, fatty acids increased notably with surplus N-nitrate, above F/2 medium content. Low irradiance and normal concentration of nitrates in the batches of Chaetoceros gracilis species produced a greater EPA content. C. constrictus, a diatom isolated from phytoplankton samples, presented higher levels of EPA and DHA at low levels of nitrogen and low irradiance.